Testing the test: exploring conceptualisations of english literature in post-16 literature assessment - Lim, Jia Wei (Penerbit Universiti Kebangsaan Malaysia, 2017)
The format of post-16 literature education assessment has not varied much since formal post-16 education began in Malaysia in the late 1950s. While it still relies heavily on the writing of literature essays, conceptualisations of literature as a school subject embedded in examination papers which are constructed by different examination boards have changed in important ways. This article argues that identifying these conceptualisations through an analysis of examination papers creates an avenue to provide a different perspective in exploring the development of literature in schools. To demonstrate this, examination papers on Shakespeare and modern literature from two examination sittings administered in Malaysia, one in the year 1968 and the other in the years 2012/2013, are analysed with a focus on whether questions are writer, text or reader-centred while considering how student response, termed outcome space, is framed. This study suggests that conceptualisations of literature have shifted in two ways: the first is a shift from a balance between writer, text and reader-centred questions to a heavy inclination towards text-centred questions which is linked to another noticeable shift in student responses to literature texts that has moved from the expression of personal meaning and interpretation of the text to the demonstration of detailed textual knowledge. Such shifts demonstrate that there is a need to consider literature assessment not only as an end-product of school subject construction but as an active representation of literature that influences the teaching and learning of the subject.